STUDY OF NUMERICAL MODELING OF SHAPE DEFORMING ZONE OF DIES, DURING DRAWING HIGH CARBON STEEL WIRE TO THE TEMPERATURE AND THE STRESS-STRAIN STATE IN THE WIRE AND DIE - Yu. L. Bobarikin; M. N. Vereshchagin; M. U. Zeluev; A. V. Vedeneev; O. I. Ignatenko (Литьë и металлургия)
Investigation by numerical modeling of influence of the form of deforming zone of die at drawing of steel high- carbon wire on temperature and strained-deformed state in wire and die is carried out.